"Drinking habits": The effects of hydration status on secondary school students during school session / Mohamad Fitri Abdul Rahaman - Abdul Rahaman, Mohamad Fitri (Faculty of Sport Science and Recreation, 2016)
The major purpose of understanding the hydration status among school students is to highlight the importance of consuming proper water intake during school session and also being applied throughout their lifetime. Hydration Status is examined by the urine specific gravity (USG), urine volume, urine colour, and body weight of the student during three different periods of the school session. A total of one hundred fifty two students (N=152) were selected via stratified random sampling had participated in this study. Results had shown that the significant different value is (p<0.05), where the mean and standard deviation of age (14.99±1.90), height (159.66::1::7.59), urine specific gravity (1.02::1::0.01), urine volume (104.79±77.37) and body mass (55.37::1::24.7), while there were no significant differences in urine colour (6.07::1::1.35) where (p>0.05). If the students are having insufficient water consumption, it will hinder their learning process during school session. Therefore, the students are having moderate dehydration due to environmental condition, heat acclimatization, and drinking behaviour. It suggested by Dietitians of Canada to consume 12 cups of water or 3 liter for men and 9 cups of water or 2.2 liter for women to maintain the body in hydrated state.